Francis J. Connell, C.Ss.R.: America's Moral Barometer - Hayes, Patrick J. (US catholic historian, 2022)
Often unappreciated by scholars, the Redemptorist Francis J. Connell (1888–1967) significantly contributed to moral theology in the twentieth century and was a key figure in the Church's encounter with modernity. This article places his life and work in a broad context, including the manualist tradition and the thought of St. Alphonsus Liguori, both in which he was formed. In his effort between the 1920s and 1960s to enable a sound and orthodox basis for Catholic teaching on numerous questions, Connell's legacy is hardly negligible. Having taught hundreds of priest-students and influenced thousands more by letter or through his numerous publications, he helped set the tone for Catholic moral thought prior to the Second Vatican Council. An analysis of his life and writings offers a nuanced understanding of the man rather than viewing him only as a conservative moralist. In the classroom, in print, and through radio and television, Connell helped shape Catholic thinking on notions of rights, medical ethics, religious liberty, and the modern state, as well as approaches to American culture's more esoteric aspects such as the morality of smoking or boxing.